2021
DOI: 10.1371/journal.pone.0246702
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the gender gap in the Spanish Wikipedia: Differences in engagement and editing practices

Abstract: Wikipedia’s significant gender bias is widely acknowledged. In this paper we analyze the Spanish Wikipedia with the aim of estimating the percentage of women editors and measuring their engagement and editing practices with respect to their men counterparts. To identify the gender of Wikipedia registered users, we analyzed both the information contained in their user profile and the information provided by users about themselves on their personal user pages. Using our own coding procedure, it is possible to id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
1
8
1
Order By: Relevance
“…Analyzing users' profiles, they found that female editors only comprised 16.1% of the profiles and only accounted for 9.0% of edits. In a previous study based on a massive content codification, we showed that female editors represent a small minority of editors involved, accounting for just 11.3% of all the editors of the Spanish Wikipedia [28,29]. This evidence is similar to that of the English Wikipedia.…”
Section: Gender Gap In Participationsupporting
confidence: 69%
See 2 more Smart Citations
“…Analyzing users' profiles, they found that female editors only comprised 16.1% of the profiles and only accounted for 9.0% of edits. In a previous study based on a massive content codification, we showed that female editors represent a small minority of editors involved, accounting for just 11.3% of all the editors of the Spanish Wikipedia [28,29]. This evidence is similar to that of the English Wikipedia.…”
Section: Gender Gap In Participationsupporting
confidence: 69%
“…Although till now the data has been obtained by survey methods, it has been reported that the percentage of female editors is between 10% and 15% or even lower in the English Wikipedia [21,30]. Nevertheless, in our previous quantitative research, we found that for those editors with a large number of edits over time, such differences were not statistically significant, or even reversed, with females outperforming male editors [29].…”
Section: Gender Gap In Participationcontrasting
confidence: 54%
See 1 more Smart Citation
“…And the same is true with respect to gender: research has documented that Wikipedia editors tend to write proportionally more about people and topics related to their own gender identity (Lam et al 2011;Hinnosaar 2019). Such self-reference to one's own gender could be generating deep biases in content selection, as several studies have shown that within Wikipedia only between 8.5% and 16.1% of editors are women (Glott, Schmidt, and Ghosh 2010;Wikimedia 2011;2012;Hill and Shaw 2013;Minguillón et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…And the same is true with respect to gender: research has documented that Wikipedia editors tend to write proportionally more about people and topics related to their own gender identity (Lam et al 2011;Hinnosaar 2019). Such self-reference to one's own gender could be generating deep biases in content selection, as several studies have shown that within Wikipedia only between 8.5% and 16.1% of editors are women (Glott, Schmidt, and Ghosh 2010;Wikimedia 2011b;2011a;Hill and Shaw 2013;Minguillón et al 2021).…”
Section: Discussionmentioning
confidence: 99%